Identification of SNP variations and different microRNA binding sites at 3-UTR region of bovine HSP90AA1 gene among different Indian breeds of cattle - DEB, RAJIB; SENGAR, GYANENDRA S; SAJJANAR, BASAVRAJ; SINGH, UMESH; SINGH, INDRA; ALEX, RANI; RAJA, T V; KUMAR, SUSHIL; ALYETHODI, R R; BHANUPRAKASH, V (The Indian Journal of Animal Sciences, 2017)
Present study was aimed to identify mutations/SNPs and predict microRNAs within the 3-untranslated region of bovine Hsp90 AA1 gene. A total of 28 mutations were identified in the 3-untranslated region of bovine Hsp90 gene among 4 indigenous zebu breeds and 1 crossbred population. Results revealed that, natural mutational changes are more in crossbred cattle compared to indigenous zebu animals and the difference was statistically significant. Prediction of microRNA binding site revealed that there are atleast 7 different micro RNAs, which may interact at 3-untranslated region of bovine Hsp90AA1 gene among different breeds of cattle investigated. Out of the 7 microRNAs, miR8882 and miR3796 were the most commonly distributed among the 4 breeds while the miR9491and miR-2277-5p were restricted to Gir and Ongole breeds respectively. While miR8882 binding site were unanimous, miR3796 showed variation among the breeds. This indicate that there exists differences in the microRNA binding sites of the 3-untranslated region among cattle breeds.